Quasi-Equivalence in Translation: Semantics and Pragmatics in Transmission of Nationally Specific Vocabulary - I. A. Lekomtseva (Tsentr nauchnykh i obrazovatelnykh proektov, 2019)
The question of quasi-equivalent relations in translation is considered. It is shown that the units of the source and target languages are in relations of asymmetry. Particular attention is paid to the fact that a significant degree of asymmetry is manifested not only in the comparison of systems of two languages, but also in the establishing correlations between the use of language units in speech, namely in the folklore and mythological context. It is shown that in the transmission of lexical units in the folklore-mythological text there are certain difficulties caused not only by the incongruence of lexical systems of two languages, cognitive and cultural complications, but also by the fact that in the folklore-mythological context a word is a unit of the secondary sign system, that is, in addition to the basic meaning, a word has a folklore-mythological one. The definition of quasi-equivalence in translation is given, this phenomenon is considered at the semantic and pragmatic levels. The article presents the results of comparative translation analysis, which can be used in courses on comparative linguoculturology, translation theory and practice to clarify the methods and principles of assessing the quality of translation, as well as the creation of comparative linguoculturological dictionaries that which do not exist today.